Purification And Characterization Of Phospomolybdate Reductase Produced By Locally Isolated Serratia Marcescens Strain Dr.Y5 - Abdul Rahman, Mohd Fadhil (2007)

(untitled)
The threat of heavy metal pollution to public health and wildlife has led to an increased in developing systems that can remove or neutralise its toxic effect in soil, sediments and wastewater. In this work, a local molybdenum reducing bacterium was isolated. This bacterium is Gram negative and identified as Serratia marcescens Strain Dr.Y5 based on Biolog ID system and 16s rRNA molecular phylogenetics studies matched 99.96% to Serratia marcescens. The isolate was originally isolated from the grounds of King Edward VII (2) primary school in Taiping, Perak. The optimum carbon source for Mo-blue production was sucrose at 1.0% concentration and optimally grown at 40 °C. While the optimum concentration for nitrogen source was 0.2(w/v) % and optimum yeast concentration was 0.05(w/v) %. The Mo-blue production were optimum at pH 6.0 with the best ratio of phosphate to molybdate giving optimum reduction was 2.9 mM to 20 mM, respectively. Molybdenum reducing activity of the enzyme extract was assayed at 865 nm using 20 mM 10:4 molybdophosphoric acid and 2 mM NADH at room temperature. Purification of phosphomolybdate reductase was done by using anion exchange on Macro Prep High Q and gel filration on Zorbax GFX-250. The enzyme was assayed using NADH or NADPH as the electron donor and phosphomolybdate as the electron acceptor. The assay was completed in less than 5 minutes and produced an intense blue color with a wavelength maximum at 865 nm. The best electron donor for the enzyme is NADH (12-MP as electon acceptor) with a maximum initial velocity, Vmax of 25.07 nmole molybdenum blue produced/min/mg/protein and a Michaelis constant, Km at 0.44 mM. The best electron acceptor substrate is 10:4 molybdophosphate, with a Km of 3.87 mM and a Vmax of 24.18 nmole molybdenum blue/min (NADH as electron donor at saturated concentrations). The phosphomolybdate reductase activity has an optimum temperature at 30 °C. At 40 °C of incubation for a period of one hour, the residual phosphomolybdate reductase activity remains 80% of the control, indicating that the enzyme is stable below 40 °C. The enzyme was inactivated rapidly at temperatures higher than 54 °C and was inactivated totally at 70 °C within 30 minutes of incubation.